Association between Menstrual Hygiene Management and School Performance among the School-Going Girls in Rural Bangladesh - Md. Sabbir Ahmed; Fakir Md Yunus; Md. Belal Hossain; Kinsuk Kalyan Sarker; Safayet Khan (MDPI AG, 2021)
Background: This study investigated the relationship between menstrual hygiene practices and academic performance among rural Bangladeshi adolescent girls. Methods: A cross-sectional survey was carried out among the 499 secondary-school-going adolescent girls in grades 7-10 (aged 11-17 years, mean ± SD = 14.04 ± 1.11 years) attending either public or private institutions in rural Bangladesh. Menstruation hygiene management (MHM) was defined based on three indicators such as (i) change materials (pads/cloths) less than every 6 h, (ii) hand washing practice with soap before and after changing pads/cloths, or not washing the external genitalia at least once per day, and (iii) using a sanitary pad or drying of re-usable cloths under direct sunlight. The MHM was categorized as poor (if not practicing or practicing only one issue), average (if practicing only two issues), or good (if practicing all of the issues). School performance was determined by the total marks obtained in their last final examination (<60% marks defined as low performance and ≥60% marks defined as good performance). Binary logistics regression models were developed at the <0.05 significance level. Results: The mean age of the participants was 12 years, where 83% reported a regular menstrual cycle pattern. Overall, prevalence of practicing poor, average, and good MHM were found to be 28.46%, 55.71%, and 15.83%, respectively. About 52% of girls reported using sanitary napkins (manufactured disposable pads), 43.4% reported using pieces of reusable cloths per occasion (multiple uses), and almost all (96.29%) reported using detergents to clean multiple-use cloths. We found 2.9 times (AOR: 2.90, 95% CI: 1.61-5.24) and 5.7 times (AOR: 5.65, 95% CI: 2.72-11.71) higher odds to achieve good academic performance among those who practiced 'average' and 'good' MHM after adjusting age, education, paternal education, occupation, maternal education, household wealth status, and respondent's knowledge of menstruation. Conclusions: Results suggested that girls' school academic performance can be improved by practicing good menstrual hygiene practices. School-based menstrual hygiene management education could be useful.